Development of a community-based network to promote smoking cessation among female smokers in Hong Kong - William H. C. Li; Sophia S. C. Chan; Zoe S. F. Wan; M. P. Wang; K. Y. Ho; T. H. LAM (BMC, 2017)
Abstract Background There is a need for population-based smoking cessation interventions targeting female smokers in Hong Kong. This study describes the development of a community-based network to promote smoking cessation among female smokers in Hong Kong. Methods Local women's organizations collaborated to launch a project to provide gender-specific smoking cessation services. In the first phase of the project, the Women Against Tobacco Taskforce (WATT) was created. In the second phase, a smoking cessation training curriculum was developed and female volunteers were trained. The third and final phase included the provision of gender-specific smoking cessation counseling services in Hong Kong. Results A need assessment survey with 623 workers and volunteers of WATT members was carried out to develop a gender-specific smoking cessation training curriculum. A 1-day training workshop to 28 WATT affiliates who provided brief cessation counseling in the community was organized. Fourteen organizations (69 service units) agreed to form a network by joining WATT to promote smoking cessation and increase awareness of the specific health risks among female smokers. Conclusions The community-based network to promote smoking cessation was effective in helping female smokers to quit smoking or reduce their cigarette consumption. The results also suggest that this community model of promoting gender-specific smoking cessation services is feasible. Trial registration Clinicaltrials.gov ID NCT02968199 (Retrospectively registered on November 16, 2016).